Analisis Perjanjian Perkawinan Dalam Membentuk Keluarga Sakinah Perspektif Hukum Keluarga Islam - Palistina, Yeka; Supardi, Supardi; Yarmunida, Miti (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2023)
Abstract : This research is to analyze the urgency of marriage agreements in forming a sakinah family, and the perspective of Islamic family law regarding marriage agreements in order to form a sakinah family. This research method is a qualitative method, with a type of library research. The results of this study are: First, the urgency of the marriage agreement in controlling the use of husband and wife's assets is that the marriage agreement has good benefits as a preventive measure in the event of a divorce because the making of a marriage agreement will facilitate the distribution of assets here and there. The marriage agreement regulates the consequences of marriage related to assets, the marriage agreement is also carried out to minimize and avoid disputes between husband and wife, as well as provide legal certainty between the rights and obligations of each party. The urgency of a marriage agreement in forming a sakinah family is to form a happy family, make a marriage agreement which includes communication issues, personal and joint property, biological needs, economic issues, and appearance. The marriage agreement includes a form of mashlaahaah for husband and wife to achieve maqaasiid asy-shari'ah. Through the marriage agreement, what is the aim of the Shari'a, namely to achieve benefit, can be realized/achieved. Second, the marriage agreement in order to form a sakinah family in the perspective of Islamic family law is to build a sakinah family, and overcome problems that arise in the family and society. The marriage agreement demands his goodness and does not demand it other than that whatever happens, mawaddah has decorated one's heart. Who owns it, he will never break ties no matter what. If so, this word carries the meaning of love, but it is love plus. The meaning of this word is similar to the meaning of the word grace. It's just that, mercy is addressed to those who are blessed, while those who are blessed are in a state of need. Keywords: Marriage Agreement, Sakinah Family, Islamic Family Law Abstrak: Penelitian ini untuk menganalisis urgensi perjanjian perkawinan dalam membentuk keluarga sakinah, dan perspektif hukum keluarga Islam tentang perjanjian perkawinan dalam rangka membentuk keluarga sakinah. Metode penelitian ini adalah metode kualitatif, dengan jenis penelitian library research. Adapun hasil penelitian ini adalah : Pertama, Urgensitas perjanjian perkawinan dalam mengantur penggunaan harta suami dan istri adalah bahwa perjanjian perkawinan mempunyai manfaat yang baik sebagai tindakan prefentif apabila terjadinya perceraian karena dibuatnya perjanjian perkawinan akan mempermudah pembagian harta gono-gini. Perjanjian perkawinan mengatur akibat perkawinan yang berhubungan dengan harta kekayaan, perjanjian perkawinan juga dilakukan untuk meminimalisir dan menghindari terjadinya perselisihan antara suami istri, serta memberikan kepastian hukum antara hak dan kewajiban masing-masing pihak. Urgensi perjanjian perkawinan dalam membentuk keluarga sakinah yakni membentuk keluarga yang bahagia, membuat perjanjian perkawinan yang meliputi masalah komunikasi, harta pribadi maupun bersama, kebutuhan biologis, masalah ekonomi, dan penampilan. Perjanjian perkawinan termasuk bentuk mashlaaha bagi pasangan suami istri untuk tercapainya maqaasiid asy-syari’ah. Melalui perjanjian perkawinan, apa yang menjadi tujuan syariat yaitu untuk mencapai kemaslahatan bisa terwujud/tercapai. Kedua, Perjanjian perkawinan dalam rangka membentuk keluarga sakinah dalam perspektif hukum keluarga Islam adalah untuk terbangunnya keluarga sakinah, dan mengatasi permasalahan yang timbul dalam keluarga dan masyarakat. Perjanjian perkawinan menghendaki untuknya kebaikan serta tidak menghendaki untuknya selain itu apa pun yang terjadi mawaddah telah menghiasi hati seseorang. Siapa yang memilikinya, dia tidak pernah akan memutuskan hubungan, apa pun yang terjadi. Jika demikian, kata ini mengandung makna cinta, tetapi ia adalah cinta plus. Makna kata ini mirip dengan makna kata rahmat. Hanya saja, rahmat tertuju kepada yang dirahmati, sedangkan yang dirahmati itu dalam keadaan butuh. Kata Kunci: Perjanjian Perkawinan, Keluarga Sakinah, Hukum Keluarga Islam